HBV variants are common in the 'immune‐tolerant' phase of chronic hepatitis B. Issue 10 (17th June 2020) - Yuen, Lilly; Revill, Peter A.; Rosenberg, Gillian; Wagner, Josef; Littlejohn, Margaret; Bayliss, Julianne; Jackson, Kathy; Tan, Susanna K.; Gaggar, Anuj; Kitrinos, Kathryn; Subramanian, Mani; Gane, Ed; et al.
Abstract: Nucleos(t)ide analogues (NUC) treatment prevents progression of liver fibrosis in subjects with chronic hepatitis B (CHB). However, risk of hepatocellular carcinoma (HCC) persists despite viral suppression. Specific HBV variants have been associated with adverse outcomes, including HCC; however, the frequency of these variants during the seemingly benign immunotolerant (IT) phase is unknown. Next‐generation sequencing and detailed virological characterization on a cohort of treatment‐naïve IT subjects were performed to determine the frequency of clinically relevant viral variants. Samples from 97 subjects (genotype B/C 55%/45%, median HBV‐DNA 8.5 log10 IU/mL, median HBsAg 4.8 log10  IU/mL, median HBeAg 3.6 log10  PEIU/mL) were analysed. Despite subjects being in the IT phase, clinically relevant HBV variants were common at baseline, particularly in the basal core promoter (BCP, overlaps the hepatitis B X (HBx) gene), precore and PreS regions. BCP/HBx variants were independently associated with lower baseline HBeAg, HBsAg and HBV‐DNA titres. Precore variants were independently associated with higher baseline ALT. Increased viral diversity was associated with increased age and lower HBV‐DNA, HBsAg and HBeAg levels. Low‐level (<5%) drug resistance–associated amino acid substitutions in the HBV reverse transcriptase were detected in 9 (9%) subjects at pre‐treatment but were not associated with reduced antiviral activity. Future studies should evaluate whether the detection of HBV variant during IT CHB is predictive of progression to immune clearance and poor prognosis, and whether early initiation of antiviral therapy during IT CHB to prevent the selection of HBV variants is clinically beneficial.